Proceedings of the 4th International Conference on Movement Computing 2017
DOI: 10.1145/3077981.3078050
|View full text |Cite
|
Sign up to set email alerts
|

Representation Strategies in Two-handed Melodic Sound-Tracing

Abstract: is paper describes an experiment in which the subjects performed a sound-tracing task to vocal melodies. ey could move freely in the air with two hands, and their motion was captured using an infrared, marker-based system. We present a typology of distinct strategies used by the recruited participants to represent their perception of the melodies. ese strategies appear as ways to represent time and space through the nite motion possibilities of two hands moving freely in space. We observe these strategies and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In the present study, stimuli construction and theory-testing of embodied responses to perceived musical motion are inextricably linked. First, we test that certain cross-modal associations between Contour and vertical motion, as observed in the embodied music perception literature (Gødoy et al , 2006; Kelkar & Jensenius, 2019; Krantz et al, 2006; Küssner & Leech-Wilkinson, 2014; Küssner et al , 2014; Nymoen et al , 2011), may be partially explained by theories of embodied vocal responses (Cox, 2017). Second, that the perception of musical events as kinetic ones, tested through Vertical Density, can be explained by theories of general embodied responses (Godøy, 2003; Leman, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, stimuli construction and theory-testing of embodied responses to perceived musical motion are inextricably linked. First, we test that certain cross-modal associations between Contour and vertical motion, as observed in the embodied music perception literature (Gødoy et al , 2006; Kelkar & Jensenius, 2019; Krantz et al, 2006; Küssner & Leech-Wilkinson, 2014; Küssner et al , 2014; Nymoen et al , 2011), may be partially explained by theories of embodied vocal responses (Cox, 2017). Second, that the perception of musical events as kinetic ones, tested through Vertical Density, can be explained by theories of general embodied responses (Godøy, 2003; Leman, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Certain CMCs are linked to perceived motion (i.e., kinetic CMCs) and thus are a form of embodied music reception. Most studies have asked participants for subjective ratings; however, there are also examples where participants have had motor responses recorded during music listening, finding a strong correspondence between pitch and vertical motion (Gødoy et al, 2006; Kelkar & Jensenius, 2019; Krantz et al, 2006; Küssner & Leech-Wilkinson, 2014; Küssner et al, 2014; Nymoen et al, 2011). The origins of this perceptual experience may arise from CMCs formed through experience with ecological stimuli (e.g., Hansen & Huron, 2019), or from internal stimuli, using the self (body/voice) as a reference point (e.g., Cox, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This perception is important for musical memory and is somewhat invariant to transposition and changes in intervals [5,14]. The act of sound tracing-moving one's hands in the air while listening to music-has been studied in music information retrieval [10,15,18,21,22]. It has been suggested that the relationship between sound tracings and pitch is non-linear [6,16].…”
Section: Related Workmentioning
confidence: 99%